Metal Complexes of Bis (2,6-diamine pyridine 2,5-hexanedione) Macrocyclic Schiff-Base Ligand: Preparation, Characterization and thermal study - Sabah , Assim A.; Ameen, Anwer M.; Al-Daher, Abdulgany (Iraqi Journal of Science, 2022)
New series of Schiff base macrocyclic complexes have been prepared through a new chemical approach. Firstly, ligand Bis (2,6-diamine pyridine 2,5-hexanedione (DP-HD) prepared via reacting of 2,6-diamine pyridine (DP) with 2,5-hexanedione(HD) in molar ration (1DP:1HD). The complexes of this ligand include Mn (II), Fe (II), Co (II), Ni (II) and Cu (II) as central metal ions also prepared with a molar ratio of (1 ligand:1 metal ion). Metals chloride was used as raw materials for this preparation. A variety of spectral and physical techniques were applied to characterize the macrocyclic complexes such as 1H-NMR, FT-IR, UV-Vis, CHN analysis, conductivity, Atomic absorption and magnetic susceptibility. Depending on spectral and magnetic measurements, the suggested geometrical shapes of these complexes were reported. FT-IR spectroscopy recorded the coordination sites based on the ligand’s main group bands that could shift to a lower frequency. Finally, thermal stability has been investigated for ligands and their complexes. While the thermal gravimetric analyses (TGA) and differential thermal analyses (DTA) approved the stability of these compounds if compared to their ligands only.